Promoting the source separation of household kitchen waste based on comprehensive evaluation and economic feasibility. (15th March 2022) - Fei, Fan; Kosajan, Vorada; Shen, Neng; Luo, Jing
Abstract: The source separation and treatment of food waste is urgent for sustainable municipal solid waste (MSW) management. Household kitchen waste (HKW) is relatively difficult to manage as large amounts are produced by dispersed sources. Although many countries and regions have begun to promote HKW source sorting, controversy over whether and how this approach could improve the comprehensive benefits of MSW management remains. This study constructed four most potential HKW source separation scenarios, and compared their energy efficiency, environmental impact and economic benefits were with the baseline full waste-incineration scenario to provide foundation for HKW management policy formation. The results showed that, when the amount of MSW stabilized, promoting HKW source separation had no significant advantages, while the overall benefits of HKW separation would be further expanded with continuous increases in the generation amount of MSW, and the economic cost would be acceptable. The suitable application conditions of different source separation modes vary. Centralized anaerobic digestion of HKW is a suitable choice for regions determined to promote long-term HKW separation, since it could reduce environmental impact by 3%–51% over the baseline scenario, and the comprehensive benefits would be further accentuated as the source separation rate increased. Small-scale on-site biochemical HKW treatment should not be widely utilized as it has high pollutant emissions and costs per-unit. Food waste disposers (FWDs) achieved outstanding waste reduction effect, and the government could guide the purchase of FWDs by residents according to the urban drainage system conditions. HKW source dewatering required the lowest cost and effort, and could be a suitable solution for regions that cannot promote strict HKW source separation. Highlights: The source separation and treatment of household kitchen waste (HKW) is urgent. Four HKW source separation scenarios were constructed, evaluated and compared. HKW separation had significant advantages when MSW amount continuous increases. The suitable application conditions of different source separation modes vary. Anaerobic digestion suits for regions need to promote long-term waste separation.